ANALYSIS OF FACTORS CAUSING PATIENT OVERLOAD DUE TO THE SIMRS BRIDGING SYSTEM WITH BPJS (ERROR/MAINTENANCE) AT A HOSPITAL - Rizky Aprilianti Lestari; Maya Aprilianingsih; Yogi Catur Putra; Fitri Yuli Mayasari; Nurbaiti Nurbaiti; Windi Pertiwi; Aulia Rahma Oktapianingtyas (Persatuan Dosen Kesehatan Masyarakat, 2026)
The Hospital Information System (SIMRS) and Virtual Claim (V-claim) are two information systems used by hospitals in servicing especially for BPJS patients. These two systems have differences that can affect the effectiveness and efficiency of the patient registration process, as staff need to use both applications to verify the BPJS participant status with the Participant Eligibility Letter (SEP). Method: This study uses quantitative research with data collection through observation and questionnaires at the registration unit of Bandar Lampung Adventist Hospital. Results: Bridging the SIMRS system with BPJS frequently encounters errors/maintenance issues, and there is still a backlog of patients when the bridging system between SIMRS and BPJS is disconnected. Conclusion: The bridging of the SIMRS system with BPJS often experiences disruptions, leading to patient congestion, which significantly impacts the workflow of the registration staff. However, the registration unit is already 50% prepared to handle this.